Papers of John Pascoe Fawkner - Fawkner, John Pascoe, 1792-1869.; Settle, David, active 1836.; Diprose, William; Wise, Charles (1803)
MS 3224 comprises: 1. "Journal of preparations for departure to and proceedings at Port Phillip" covering the period from 18 July, 1835, when John Pascoe Fawkner purchased the schooner "Enterprise" and left Launceston on 21 July, to the final entry on 3 August, 1836. The journal was kept by Fawkner on board the schooner "Enterprise". Also included in this volume are the directions for Mr J.C. Underwood regarding business matters; a brief summary of reasons behind the purchase of the "Enterprise" and his contact with Aborigines from Port Phillip; a list of stock at Pascoe Vale, February 1843; lists of various items from novels to newspapers; and, the agreement between Fawkner, William Diprose and Charles Wise, dated 6 August, 1836.
2. Stores book, 1837-1838, which also contains copies of letters and details of freight carried on the "Enterprise", 1837-1839. 3. Five notebooks. 4. Diary, 1867. 5. Facsimile copies of The Melbourne advertiser, v. 1, no. 1, (1 Jan. 1838) and v. 1, no. 2 (8 Jan. 1838). Also, a statement of timber account, 1840 (3 clamshell boxes, 2 folders).
Manuscript reference no.: MS 3224.
Guide to collections of manuscripts relating to Australia
Stores book also available on microfilm at the National Library of Australia Main Reading Room – Newspapers and Family History at mfm G 24756.
State Library of Victoria.
State Library of New South Wales.
John Pascoe Fawkner was an early pioneer, businessman and politician of Melbourne. As the owner of the schooner “Enterprise”, he was involved in the settlement of Port Phillip district from August 1835. In 1838, he published the district’s first newspaper, The Melbourne advertiser. Fawkner was a leading figure in the new colony and served as a member of the Legislative Council from 1851 until his death in 1869.
Keywords: Fawkner, John Pascoe, -- 1792-1869 -- Archives; Underwood, J. C; Enterprise (Schooner); Pioneers -- Australia -- Archives; Land settlement -- Victoria; Aboriginal Australians -- Victoria; Australian newspapers -- Victoria -- Port Phillip Region; Port Phillip Region (Vic.) -- Newspapers; Port Phillip Region (Vic.) -- Discovery and exploration; Victoria -- History -- 1834-1851.; Victoria -- Periodicals; Graziers; Pioneers; Business professionals; Newspaper proprietors; Politicians